Monitoring the distribution and development of apple scab (Venturia inaequalis) and powdery mildew (Podosphaera leucotricha) disease in the southern and southeast regions of Kazakhstan - Galymbek, K.; Madenova, A.K.; Bakirov, S.B.; Kabylbekova, B.Zh.; Irkitbay, A.; Aitymbet, Zh.; Kaldybayeva, D.I.; Abdikarimova, R.; Munira, Bolat (Fundamental and Experimental Biology, 2023)
Apple (Malus domestica) is a very important fruit tree that is widely cultivated in different climatic regions of the world. Scab (Venturia inaequalis (Cooke) G.) and powdery mildew (Podosphaera leucotricha) are common fungal diseases in apple orchards. The harmful impact of these disease results in poor fruit size and quality, premature fruit fall, peeling, less fruit bud development in the next year’s fruit buds. When the patho-gen is present under favorable environmental conditions, disease develops highly, and the crop losses of up to70 %. Phytosanitary monitoring for the spread and development of the scab and powdery mildew pathogen was carried out the main fruit tree-growing regions of Kazakhstan, namely, Almaty, Turkestan and Zhambyl regions apple-growing farms in 2022. Research was conducted on apple orchards on the territory of 14 ha in Almaty region, 288 ha in Turkestan region and 40 ha in Zhambyl region. We carried out a phytopathological assessment of fungal disease for folowing commercial varieties Starkgrimson, Zolotoy presvesov, Aydaret, Americanka, Samured, Gala, Fuji and Golden Delicious grown in these regions. According to the results of the study, there were no symptoms of powdery mildew in Almaty and Zhambyl regions. Furthermore, pow-dery mildew distribution was 18.05 % in the Aidaret, while its development was at a lower level of 3.06 % in the apple orchards where Tulkibas district of Turkestan region. Scab pathogen is present in all orchards of the studied regions. The pathogen Venturia inaequalis was spread at an average level with 23 -31 % in Starkgrim-son, Zolotoy presvesov and Aidaret varieties, while its development was at a low level with 1-2.84 % in the Almaty region. The disease distribution is with 30-37 % of orchards where Starcrimson, Golden Delicious and Red Delicious varieties are grown in the Zhambyl region. As well as the development of the disease was 2-4.12 %. In the Turkestan region, in Samured and Starkrimson varieties, scab ditribution was at a low level with 3-3.71 %, while the development of the disease was with 0.50-0.81 %. In Idared and Gala varieties, the disease distribution in the range about 16-17 %, while the development developed at a lower level with 0.13-1.25 %. The Fuji was recognized as resistant variety to scab, for the reason of no disease symptoms.